The weldability of AISI 4340-AISI 2205 steels using friction welding - Caligulu, U.; Yalcinoz, M. (Natl Inst Optoelectronics, 2015)
In this study, the weldability of AISI 4340-AISI 2205 steels using friction welding was investigated. AISI 4340 tempered steel and AISI 2205 duplex stainless steel each of which had a 12 mm diameter were used to fabricate the joints. The friction welding tests were performed by using a direct-drive type friction welding machine. After friction welding, interface regions of the welded specimens were examined by OM, SEM, EDS and X-Ray analysis to determine the microstructure changes. Microhardness and tensile tests were conducted to determine mechanical properties of the welded specimens. The experimental results indicated that AISI 4340 tempered steel could be joined to AISI 2205 duplex stainless steel using the friction welding technique for achieving a weld with sufficient strength. Tensile strength values also confirmed this result and intermetallic phases did not occur at the interface. The maximum tensile strength of 624.89 MPa could be obtained for the joints welded under the welding conditions as follows; of rotation speed of 2200 rpm, friction pressure of 30 MPa, forging pressure of 60 MPa, friction time of 6 s and forging time of 3 s.
Keywords: AISI 4340; AISI 2205; Friction Welding; Microstructure; Tensile Strength